2008
DOI: 10.1007/s00216-008-2476-z
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic separation of humic substances using hydroxyethyl cellulose as a buffer additive and its application to characterization of humic substances in a river water sample

Abstract: We have developed a concise tool for the investigation of the transition of humic substances in environmental water. The separation of water-soluble humic substances was achieved rapidly and effectively by capillary electrophoresis using a polyacrylamide-coated capillary and a phosphate electrophoretic buffer solution (pH 7.0) containing hydroxyethyl cellulose. The separation mechanism was assessed using the ultrafiltration technique. The effect of the complexation of humic substances with metal ions was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…12 Of course, the proposed method would be applicable for the investigation of interactions of humic substances with coexisting materials including metal ions. The separation performance on the separation of 0.1 -2 kbp of DNA ladder by the proposed method showed that separation by the proposed method basically undergoes the molecular sieving effect of the mixed-polymer medium and that the proposed method was also applicable for the separation of analytes other than humic substances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Of course, the proposed method would be applicable for the investigation of interactions of humic substances with coexisting materials including metal ions. The separation performance on the separation of 0.1 -2 kbp of DNA ladder by the proposed method showed that separation by the proposed method basically undergoes the molecular sieving effect of the mixed-polymer medium and that the proposed method was also applicable for the separation of analytes other than humic substances.…”
Section: Discussionmentioning
confidence: 99%
“…12 On the other hand, it was found that the addition of PEG 10000 to the electrophoretic buffer solution slightly improved CE resolution. 20 An electrophoretic buffer solution containing both HEC and PEG 10000 was, therefore, tested as the first candidate for the solution that served as both the separation medium and the dynamic coating agent in this study.…”
Section: Dynamic Coating Ce With Non-ionic Polymers With Hydrogen Bonmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally different electrophoregram profiles and migration times of humic and fulvic acids have been used to distinguish between young, old, autochthonous and allochthonous natural organic matter. Sometimes, especially isotachophoresis is used to isolation of humic substances fractions (TAKAHASHI et al, 2009, NAGYOVA et al, 2001.…”
Section: Soil Organic Matter Analytical Methodsmentioning
confidence: 99%